Transforming Education for Juvenile Offenders in Child Special Guidance Institutions - Risky Waldo; Herman Bakir (Publikasi Indonesia, 2024)
Problems faced by juvenile offenders in the Special Child Guidance Institution (LPKA) include limited educational facilities, lack of qualified educators, and lack of external support. These problems are exacerbated by the psychological challenges experienced by these children, which have a negative impact on their learning process. Therefore, the transformation of education in LPKA is an urgent need to support their rehabilitation and social reintegration. This study aims to analyze the implementation of education for juvenile offenders in LPKA by mapping the challenges faced and evaluating the efforts that have been made to overcome them. The main focus includes the development of an adaptive, inclusive, and technology-based education model to create a learning environment that supports children's holistic development. The method used is a normative legal approach with policy analysis. Data were collected through literature studies, analysis of related regulations, and studies of educational practices in LPKA that have been implemented. The results of the study indicate that the implementation of education in LPKA still faces significant obstacles, especially related to facilities, human resources, and less than optimal policy support. However, there is potential for improvement through strengthening collaboration between institutions, providing training for educators, and developing relevant life skills-based programs. The implications of this study emphasize the importance of education policy reform that is more responsive to the needs of adolescents in LPKA. Regulations are needed that strengthen the guarantee of equal and quality education, intensive training for educators, and curriculum development that emphasizes character education and life skills. Thus, it is hoped that adolescents in LPKA can obtain decent education and have the opportunity for better social reintegration.